Gambaran Job Safety Analysis Survey Jalur Instalasi Outdoor Di Biznet Cirendeu Tahun 2025 - Ega Oktavia; Munaya Fauziah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Millions of workers die or are injured every year. The telecommunications sector, including internet access installation, faces high hazards such as heights and electricity. Job Safety Analysis (JSA) is a crucial tool for identifying hazards and controlling risks. This study aims to determine the description of JSA implementation in outdoor internet access installation survey work at Biznet Cirendeu in 2025. This descriptive observational qualitative research uses in-depth interviews with key informants (HSE Officer) and main informants (field technicians), direct observation with a checklist, and internal JSA document review. Source and method triangulation are used for data validity. Identified potential hazards include fall risks, electric shock, ergonomic injuries, and contact with sharp objects. The likelihood of incidents is generally small to moderate, but the severity can vary from mild to fatal. Risk control has been applied through PPE and administrative controls, but there are still challenges in compliance and optimization of engineering/substitution controls. The implementation of JSA at Biznet Cirendeu has followed the stages of risk identification, assessment, and control, but requires strengthening worker compliance and developing higher controls. It is recommended to improve PPE/SOP supervision, optimize engineering/substitution controls, update JSA documents, and strengthen OHS culture.